Advertising, celebrity and the effect to purchase intention of Camera Canon Mirrorless M50 - Ressa Fahlevi; Susi Evanita; Whyosi Septrizola (Universitas Negeri Padang, 2021)
This study aims to analyze: (1) The effect of advertising on consumer buying interest for Canon Mirrorless M50 cameras in Padang City. (2) The effect of commercials on consumer buying interest for the Canon Mirrorless M50 camera in Padang City.This research is a causative research. The population in this study are people in the city of Padang who have seen the Canon Mirrorless M50 camera advertisement on YouTube with a sample of 100 people. The sampling technique used was accidental sampling technique which is a non-probability sampling method. The types of data in this study are primary and secondary data. Data analysis using multiple regression analysis test.The results of this study indicate that: 1) Advertising has a significant effect on consumer buying interest for the Canon Mirrorless M50 camera in the community in Padang City, 2) Star advertisements have a significant effect on consumer purchase interest for the Canon Mirrorless M50 camera in the community in Padang City.